Lichen (Jhula) - Livelihood Potential, Market Survey and Value Chain in Uttarakhand - Maikhuri, Seema; Kaur, Ajeet; Napalchyal, Siddharth; Dobhal, Kanchan (Indian Forester, 2019)
Uttarakhand has half of its population in the rural areas which is dependent on surrounding forests for a part of its living. Lichen (Jhula) which consists of two unrelated organisms, a fungus and an alga growing in symbiotic association, is an important non-timber forest produce providing livelihood to inhabitants of hills in Uttarakhand. It finds uses in preparation of perfumes, dyes, ayurvedic medicines and condiments. A collector may gather 3.5 – 7.0 Kg Jhula in a day. A local trader (middlemen) may collect the produce from about 15-20 primary collectors after paying `25-5+0/Kg to them depending on the quality. Approximately 750 metric tons of lichen is collected from Uttarakhand hills annually which is sold through open auction at three herbal mandis of Uttarakhand Forest Development Corporation. Due to proximity to the lichen collection areas, Ramnagar and Rishikesh mandis attract more middlemen and traders. Collection price of Jhula has 62% share in total expenses incurred whereas a trader earns 131% profit by selling it. For the collectors, it is the second highest income generating activity after agriculture in Jhula rich areas. The harvesting method being adopted currently is on rotational manner which poses a big obstruction for the development of Jhula sector as big livelihood opportunity.There is a need to allow regular harvesting and properly channelizing the lichen sector through tendering and marketing from forests to mandis in order to enhance the livelihood of the collectors which will also be helpful to check the migration of local population towards the plains.